PROJECT SCHEDULING ANALYSIS USING THE CRITICAL PATH METHOD – CASE STUDY: SUBSIDIZED HOUSE CONSTRUCTION PROJECT IN HILL MULYA HOUSING, SAMARINDA CITY - Rakasyiwi, Gilang Ramadhan; Witjaksana, Budi; Tjendani, Hanie Teki (Transpublika Publisher, 2022)
Samarinda City has a total of 123 housing estates with 20 subsidized housing (MBR) and 4 mixed housing. Project scheduling in construction greatly determines the project's success because it is a benchmark that the project is successful within the allotted time. CPM (Critical Path Method). CPM is a method that introduces an element of project time by using a predefined activity time estimate. This method is used for crushing the Bukit Mulya housing project, which only applies to the implementation of crash time. From the analysis results, the initial scheduling time, which was originally 87 days, was trimmed by 9 days using CPM, the optimal time was 78 days.